Pengembangan Sumber Daya Manusia di Dalam Meningkatkan Etos Kerja Perangkat Desa Karang Sari, Lampung - Eva Nurhaidah,; Widiana Indah Permata (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the development of human resources in improving the work ethic of village officials in Karang Sari Village, Lampung. The respondents in this study were 10 village officials, namely the village head, village secretary, finance head, general and planning head, village operator, six n g operator, government section, welfare section, hamlet head, and service section. The data collection methods used were observation, interview, and documentation. The collected data were analyzed descriptively by reducing data, presenting data, and drawing conclusions. The results of research conducted by conducting interviews show that human resource development in improving the work ethic of village officials in Karang Sari, Lampung is good but still requires improvement, indicated by work rotation in Karang Sari village has not been implemented, but it does not rule out the possibility of work rotation, pre-work instruction training is always held once a year, internships at the village office are always open to the public, briefings at the village office are often carried out and almost every week, and there are temporary assignments for certain parts. For the obstacles to human resource development in improving the work ethic of village officials in Karang Sari, Lampung, namely the unpreparedness and lack of knowledge of human resources so that there has been no work rotation, lack of responsibility and discipline at work so that the implementation of pre-work instructions is disrupted, neglect and lack of attention and socialization in internship activities, lack of understanding possessed by village officials and a monotonous mindset in the briefing process and the lack of knowledge and low quality of human resources in the temporary assignment process. Keywords: Human Resource Development, Work Ethics